Voice care and acoustic characteristic in students of acting and other sudents - Varošanec-Škarić, Gordana (Array, 2006)
Gordana Varošanec-Škarić University of Zagreb, Faculty of Humanities and Social Sciences, Dpt. of Phonetics gvarosan@ffzg.hr VOICE CARE AND ACOUSTIC CHARACTERISTICS IN STUDENTS OF ACTING AND OTHER STUDENTS On the basis of the data collected with the questionnaire about voice history (adapted from: Ford, 1994)  2 test was used to investigate the difference between a group of future elite voice professionals, students of acting (n = 45) and other students (n = 45). T-test was used to calculate differences between the two groups in acoustic parameters as measured by the Praat software. These acoustic variables comprised: f0 mean, f0 minimum and maximum, s f0, local jitter and shimmer and HNR. The acoustic variables were measured in the middle part of three sustained phonations of the vowel /a/ and then averaged. Additionally, standard deviation means of the complete phonations were calculated. In order to illustrate the timbre LTASS (the AS software) was extracted for each voice recorded by means of the standard test for voice assessment with the total duration of about 70 seconds (Škarić 1994, Varošanec-Škarić 1997). The results showed that the group of students of acting most significantly differed from the group of other students in the variables of voice use, of past voice history and in and personal life style. In past medical history actors were significantly more ill. The nature of these differences was also interesting: it was expected that students of acting spent significantly more time practicing voice exercises, that they took more acting instructions, generally spoke more in larger rooms (p<0.00001) and did warm up exercises (p=0.0003). But it was not expected that they smoked in larger percentages (p=0.003) then non professionals and that they drank alcoholic drinks as much as other students. Acoustically, male smokers showed significantly lower average f0 values as well as f0 minima and maxima (p<0.001). They had an increased local jitter (0.51%:0.342%) and shimmer (0.290dB:0.277dB) when compared with non smokers. However, these differences were not statistically significant and the average jitter and shimmer values were below the threshold for pathology (jitter: 1.040 % ; shimmer: 0.350 dB). Female smokers had significantly lower f0 maxima (p=0.04), non-significantly lower pitch, while jitter and shimmer even showed non-significantly lower values then in female non smokers. This could be explained by the fact that they smoked less then their male counterparts while paying more attention to voice care. Male students of acting had significantly lower f0 standard deviation means (p=0.015), because the total duration of phonation was taken into account which means that they had a more stable pitch throughout the phonation. They also showed a significantly higher HNR (p=0.001) when compared with other students. Female students also showed a significantly higher HNR (p=0.01), having more harmonic sound in their voice. They had a non-significantly lower jitter (0.271%:0.356%) ; p=0.06) and shimmer (0.202 dB: 0.257 dB ; p=0.08). The data could be used when working with professional voice users. The data showed the importance of the appropriate use of voice which reflected relatively good voice quality despite the bad living habits of the future professional voice users.